Building a collaborative solution in dense urban city settings to enhance parcel delivery: An effective crowd model in Paris. (November 2018) - Akeb, Hakim; Moncef, Btissam; Durand, Bruno
Highlights: We study the use of crowd logistics to deliver parcels in dense urban cities. We developed a model based on circle packing. The solution uses the neighbors to collect and deliver the parcels in case the customer is away from home. An experiment was conducted in the 12th district of Paris (France). Abstract: Parcel delivery, one of the major components of e-commerce growth, has become increasingly challenging with the increase of urban logistics issues. During home delivery, many parcels may be returned if the customer is away from home, generating additional costs. In this paper, we propose a solution based on the crowd that consists to collect and deliver parcels using individuals (neighbors). The method uses circle packing to estimate the number of neighbors needed, the number of parcels they have to manage and the corresponding reward. An experiment was conducted on the 12th district of Paris (France) dataset. Encouraging results were obtained.